THE EFFICACY OF COCOA BEAN EXTRACT MOUTHWASH CONCENTRATION IN REDUCING PLAQUE INDEX IN THE ORAL CAVITY AMONG PRIMARY SCHOOL STUDENTS AT SDN KAYEE LEU, INGIN JAYA SUBDISTRICT, ACEH BESAR - Mardiah, Ainun; Nuraskin, Cut Aja; Salfiyadi, Teuku; Reca, Reca; Rahmayani, Liana; Usrina, Nora; Setya Ningsih, Diana (International Journal of Research -GRANTHAALAYAH, 2024)
Oral and dental diseases have a high prevalence in Indonesia, with 88.8% of the population experiencing dental caries and periodontitis. Dental plaque is a soft deposit that tightly adheres to tooth surfaces and is composed of microorganisms that contribute to the development of dental caries. Preventing caries and controlling plaque can be achieved through the use of mouthwash, which is more effective when herbal mouthwash containing antioxidants and antibacterial agents is used. Cocoa bean extract (Theobroma Cacao L.) contains secondary metabolites such as alkaloids, flavonoids, tannins, steroids, and exhibits antibacterial and anti-inflammatory properties, as well as strong inhibitory effects against S. mutans bacteria. The objective of this study is to determine the effectiveness of cocoa bean extract mouthwash concentration in reducing the plaque index in the oral cavity. The research methods included laboratory experiments and quasi-experiments with a post-test only control group design. The research was conducted at the Faculty of Veterinary Medicine laboratory, University of Syiah Kuala, and SDN Kayee Leu, Aceh Besar, involving 30 students. Data analysis was performed using ANOVA in the SPSS program. The results of the study indicate that the phytochemical analysis of cocoa bean extract contains alkaloids, steroids, terpenoids, saponins, flavonoids, phenols, and tannins. The Minimum Inhibitory Concentration (MIC) of cocoa bean extract mouthwash on the growth of Streptococcus mutans was observed at a concentration of 1%, and no Minimum Bactericidal Concentration (MBC) was found in this study. The 1% and 2% concentrations of the mouthwash effectively removed plaque compared to the 0% concentration. In conclusion, the use of cocoa bean extract mouthwash is effective in reducing the plaque index. Further research should consider clinical trials to explore its potential as an herbal remedy.